The Effect of SIRT3/Ac-SOD2 Mediated Oxidative Stress and HCN1 Channel Activity on Anesthesia/Surgery Induced Anxiety-Like Behavior in Mice - Miao, Hui-Hui; Liu, Qiang; Wang, Ning; Liu, Yan-Ping; Chen, Chen; Wang, Hai-Bi; Huang, Hui; Wu, Wei-Feng; Lin, Jia-Tao; Qiu, Yong-Kang; Zhang, Chuan-Wu; Zhou, Cheng-Hua; et al. (Frontiers in Medicine, 2022)
Anxiety disorders are the most common psychiatric diseases, and perioperative factors often increase the incidence of anxiety. However, the mechanism and treatment for perioperative anxiety, especially anesthesia/surgery-induced postoperative anxiety, are largely unknown. Sirtuin 3 (SIRT3) which located in the mitochondria is the NAD-dependent deacetylase protein. SIRT3 mediated oxidative stress is associated with several neuropsychiatric diseases. In addition, hyperpolarization-activated cyclic nucleotide-gated 1 (HCN1) channel is also reported involved in anxiety symptoms. The purpose was to assess the role of SIRT3 on postoperative anxiety like behavior in C57/BL6 mice. We found that SIRT3 level reduced and HCN1 expression level increased in mice medial prefrontal cortex (mPFC) as well as anxiety like behavior postoperatively. In interventional research, SIRT3 adeno-associated virus vector or control vector was injected into the mPFC brain region. Enzyme-linked immunosorbent assay, immunofluorescence staining, and western blotting were employed to detect oxidative stress reactions and HCN1 channel activity. SIRT3 overexpression attenuated postoperative anxiety in mice. Superoxide dismutase 2 (SOD2) acetylation levels, SOD2 oxidative stress activity, mitochondrial membrane potential levels, and HCN1 channels were also inhibited by SIRT3 overexpression. Furthermore, the HCN1 channel inhibitor ZD7288 significantly protected against anesthesia/surgery-induced anxiety, but without SIRT3/ac-SOD2 expression or oxidative stress changes. Our results suggest that SIRT3 may achieve antianxiety effects through regulation of SOD2 acetylation-mediated oxidative stress and HCN1 channels in the mPFC, further strengthening the therapeutic potential of targeting SIRT3 for anesthesia/surgery-induced anxiety-like behavior.